DYEING POTENTIAL OF THE IRIS SIBIRICA L. FLOWERS - Pavol Kaššák; Magdalena Kuli (European Scientific Journal, ESJ, 2014)
This article put together results from several experiments which led to the measuring of the color of Iris sibirica L. flowers and using them as dye for coloring cloth. In first phase of our experiments we use the RHS color chart to measure the color of the flowers on the plant, the HPLC DAD to compare presence of six anthocyanin colorants with the methanolic extract from the flowers. We also did several tests to prove presence of basic plant metabolites groups in the iris flowers. In second phase we used the iris flowers to dye cotton cloth. We measured the cloth color by the RHS color chart and by the Konica Minolta Spectrophotometer the day after dyeing and the RHS color chart to measure it again after 6 months. Our results show high potential for the usage of the Iris sibirica L. flowers as a source for cloth dyeing.